The Role of Online Misinformation and Fake News in Ideological Polarization: Barriers, Catalysts, and Implications - Au, Cheuk Hang; Ho, Kevin K. W.; Chiu, Dickson K.W. (Information systems frontiers, 2022)
In recent years, the circulation of online misinformation and fake news has drawn our attention, given it has ideologically polarized society and has led to social instability, compromised democracies, and other consequences. Efforts on technical or behavioral dimensions on their identification are not uncommon, but these efforts inadequately addressed their roots, and thus may not stop them from creation or spreading. Using the theoretical lens of computer-mediated communications, we analyzed the ideological polarization phenomenon in Hong Kong, which has been worsening since the Umbrella Revolution in 2014. We proposed a three-stage model to illustrate the mechanism of how online misinformation and fake news leads to ideological polarization. The catalysts and barriers in each stage were also highlighted. Our analyses generate a better understanding of the mechanisms that help hinder the circulation of online misinformation and fake news, and thus, reduces the damages it caused.